Don't count me out : a Baltimore dope fiend's miraculous recovery - Alvarez, Rafael, 1958- (Culture and politics of health care work., 2022)
"This biography chronicles the life of Bruce White from the beginnings of his drug use in elementary school through the criminal acts fueled by his need for drugs to his unlikely recovery three decades later and involvement in the treatment of addicts, where he is now a leader in the rehabilitation field. Bruce White commissioned Rafael Alvarez to write his story with the hope that people who are dealing with the fallout of addiction could be inspired by the no-holds-barred recounting of his journey."--